ANANALYSIS OF ONLINE LEARNING PROBLEMS AGAINST EDUCATOR AND STUDENT CHARACTER - Mardhatillah Mardhatillah (Sensei International Journal of Education and Linguistic, 2022)
Educator and character is an embodiment in achieving a generation that is intelligent and able to have morals and personalities that are useful for the Indonesian nation. The success of education is seen from how big their character is when they can balance their cognitive, affective and psychomotor to become perfect human beings. In 2020 there was a Covid - 19 pandemic which caused everything to change, learning carried out in schools changed according to government regulations carried out at home online or learning remotely. The research being carried out now is descriptive qualitative with a literature study that seeks to provide an overview of solutions to online learning problems for the character education of students in junior high schools. This paper presents the problems of online learning, the impact of online learning on student character education, solutions and problem solving. This research uses literature study / literature study, by examining several research results, articles, books and case studies that occur in the field.